2013
DOI: 10.4315/0362-028x.jfp-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antibiotic Susceptibility of Vibrio vulnificus in Retail Shrimps in Hangzhou, People's Republic of China

Abstract: Vibrio vulnificus is a gram-negative bacterium that occurs naturally in estuarine and marine water and is associated with wound infections or septicemia related to the consumption of raw shellfish in humans. The molecular characteristics and antibiotic susceptibilities of V. vulnificus strains in shrimps from retail markets in Hangzhou, People's Republic of China, were investigated in this study. Thirty-three samples were positive for V. vulnificus in 78 shrimp samples which were collected from 15 retail marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Consistent with previous reports, a high prevalence of resistance to ampicillin was observed in all Vibrio spp. isolates in our study (Banerjee & Farber, 2018; Chiou, Li, & Chen, 2015; Hernández‐Robles et al., 2016; Li et al, 1999; Pan et al., 2013), and this resistance is usually due to the presence of a bla CARB gene (Chiou et al., 2015; Li et al., 2016). The bla CARB ‐ like genes have been found in V. cholerae predating the introduction of penicillins (Dorman et al., 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with previous reports, a high prevalence of resistance to ampicillin was observed in all Vibrio spp. isolates in our study (Banerjee & Farber, 2018; Chiou, Li, & Chen, 2015; Hernández‐Robles et al., 2016; Li et al, 1999; Pan et al., 2013), and this resistance is usually due to the presence of a bla CARB gene (Chiou et al., 2015; Li et al., 2016). The bla CARB ‐ like genes have been found in V. cholerae predating the introduction of penicillins (Dorman et al., 2019).…”
Section: Discussionmentioning
confidence: 77%
“…The superiority of tetracycline is thought to be related to its ability to inhibit protein synthesis of the pathogenic extracellular enzymes (e.g., proteases and lipases) (Fang, 1992). Unfortunately, recent studies (Labella et al, 2013;Pan et al, 2013) found that both V. parahaemolyticus and V. vulnificus developed resistance to tetracycline.…”
Section: Treatment Of V Vulnificus and V Parahaemolyticus Infectionmentioning
confidence: 99%
“…Pan et al (2013) tested the antibiotic susceptibilities of the V. vulnificus strains isolated from retail shrimps in Hangzhou, People's Republic of China to 21 antibiotics. Some strains showed resistance or intermediate resistance to cefepime (3.03%), tetracycline (6.06%), aztreonam (24.24%), streptomycin (45.45%), gentamicin (93.94%), tobramycin (100%), and cefazolin (100%).…”
mentioning
confidence: 99%
“…The findings showed that they were resistant or intermediately resistant to cefepime (3.03%), tetracycline (6.06%), aztreonam (24.24%), streptomycin (45.45%), gentamycin (93.94%), tobramycin (100%), and cefazolin (100%). Fortunately, all the isolates obtained were sensitive to ampicillin, ampicillin-sulbactam, piperacillin-tazobactam, cephalothin, ceftriaxone, cefetaxime, ceftazidime, imipenem, ciprofloxacin, levofloxacin, nalidixic acid, trimethoprim-sulfamethoxazole, chloramphenicol, and nitrofurantoin (Pan et al, 2013). …”
Section: Healthcare Burdenmentioning
confidence: 99%